LEGAL ANALYSIS OF LAND OWNERSHIP TRANSFER THROUGHT RELEASE OF RIGHTS WITH COMPENSATION (PHGR) (Case Study of Decision Number 275/PDT.G/2020/PN Mdn) - Sayyida Faradiba Vahlevi; Hasim Purba; Sutiarnoto (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
Transfer of land rights can be done in various ways, one of which is through Transfer of Land Rights with Compensation (PHGR). Article 1338 paragraph 3 of the Civil Code states that an agreement must be carried out in good faith. Good faith when making an agreement means honesty. One of the legal issues regarding the transfer of land rights with compensation in the Medan District Court Decision Number: 275 / Pdt.G / 2020 / PN Mdn, in conjunction with the Medan High Court Decision Number: 370 / Pdt / 2021 PT MDN, in conjunction with the Supreme Court Decision Number: 4259 K / Pdt / 2022. The issues raised in this decision are: What are the legal consequences of the transfer of land rights based on the release of rights with compensation, how is the legal protection of the parties against the transfer of land rights with compensation that is transferred by borrowing a name and how is the analysis of the considerations of the Medan District Court Judge in Case Number 275 / Pdt.G / 2020 / PN Mdn in conjunction with Decision No. 370/Pdt/2021/PT MDN jo. Decision No. 4259 K/Pdt/2022. The research method used is normative juridical with a descriptive analytical approach. The data used are secondary data, including primary, secondary, and tertiary legal materials. Data collection was carried out through literature studies and interviews. The analysis was carried out qualitatively by drawing deductive conclusions to answer the research problems. The results of this study are known The legal consequences of the transfer of land rights with compensation are valid and transferred so that the recipient can use and take maximum benefits from the land they own, but this must meet the provisions of the elements of Article 1320 of the Civil Code. Legal protection for the parties against the transfer of land rights with compensation that is transferred by borrowing a name consists of 2 (two) forms, namely the first preventive legal protection is by registering the land, the second repressive legal protection through the General Court. Legal protection for holders of land rights that have not been certified in good faith as regulated in Article 24 and Article 32 of PP 24 of 1997 concerning Land Registration, namely being able to file complaints, objections and lawsuits through the court. and the Panel of Judges rejected the cassation application, while the legal consideration of the judge was that the Judex Facti Decision of the Medan High Court did not conflict with the law and/or statutes.